Insecticidal Efficacy of Diatomaceous Earth and Botanical Powders against Pulse Beetle, Callosobruchus analis F. in Stored Mung Bean (Vigna radiata L.) - Muhammad Naeem; Rashid, Mamoon-ur-Rashid (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The pulse beetle is the most damaging insect pest of legumes causing huge economic losses. The experiment was conducted to find out the insecticidal effects of diatomaceous earth (DE) combined with three botanical powders in three different combinations of 25% plant powder with 75% DE, 50% plant powder with 50% DE and 75% plant powder with 25% DE. The results indicated that the least number of adult beetles settled on grains treated with T9 (75% GP + 25% DE and T3 (75% NP + 25% DE) whereas maximum number of adult beetles settled in T4 (25% TP + 75% DE). After 168 hours, all the treatments showed significant mortality (100%) of adult beetles compared to control (43%). All the treatments reduced the number of eggs (3.60 to 6.80 eggs per 20 grains) in comparison to control (17.00). The maximum (28.80) days to adult emergence were documented in T9 whereas; minimum (21.40) days were recorded in untreated grains. Among all the treatments, T9: showed minimum emergence (36.40) of adult beetles whereas; the maximum (125.20) adults emerged in control. The lowest grain damage (5.50%) was observed in T9 as related to the maximum grain damage (28.96%) in the untreated control. The minimum weight loss (3.49%) was recorded in T9. The maximum weight loss (21.08%) was recorded in untreated grains. The use of diatomaceous earth in combination with garlic powder is recommended for the management of pulse beetle under storage conditions.